Cactus Thorn-Inspired Janus Nanofiber Membranes as a Water Diode for Light-Enhanced Diabetic Wound Healing - Wen, Mei; Yu, Nuo; Zhang, Xiaojing; Zhao, Wenjing; Qiu, Pu; Feng, Wei; Chen, Zhigang; Chen, Yu; Zhu, Meifang (Nano-Micro Letters, 2026)
Diabetic wounds present challenges in clinical management due to persistent inflammation caused by excessive exudate infiltration. Inspired by the gradient wettability of cactus thorn, this study has devised a biomimetic Janus nanofiber membrane as a water diode, which endows with gradient wettability and gradient pore size, offering sustainable unidirectional self-drainage and antibacterial properties for enhanced diabetic wound healing. The Janus membrane is fabricated by depositing a hydrophilic polyacrylonitrile/chlorin e6 layer with smaller pore sizes onto a hydrophobic poly(ε-caprolactone) with larger pore sizes, thereby generating a vertical gradient in both wettability and pore structure. The incorporation of chlorin e6 in the upper layer enables the utilization of external light energy to generate heat for evaporation and produce reactive oxygen species, achieving a high sterilization efficiency of 99%. Meanwhile, the gradient structure of the Janus membrane facilitates continuous antigravity exudate drainage at a rate of 0.95 g cm−2 h−1. This dual functionality of effective exudate drainage and sterilization significantly reduces inflammatory factors, allows the polarization of macrophages toward the M2 proliferative phenotype, enhances angiogenesis, and accelerates wound healing. Therefore, this study provides a groundbreaking bioinspired strategy for the development of advanced wound dressings tailored for diabetic wound regeneration. Highlights: 1 Photonic-powered Janus membrane with dual-gradient architecture for efficient wound exudate drainage and evaporation. 2 Photodynamic–photothermal Janus membrane for enhanced bacterial eradication. 3 Multifunctional Janus membrane with dual drainage–sterilization functions accelerates diabetic wound healing via macrophage reprogramming and tissue regeneration.